Altered Fermentation Performances, Growth, and Metabolic Footprints Reveal Competition for Nutrients between Yeast Species Inoculated in Synthetic Grape Juice-Like Medium - Rollero, Stephanie; Bloem, Audrey; Ortiz-Julien, Anne; Camarasa, Carole; Divol, Benoit (Frontiers in Microbiology, 2018)
The sequential inoculation of non-Saccharomyces yeasts and Saccharomyces cerevisiae in grape juice is becoming an increasingly popular practice to diversify wine styles and/or to obtain more complex wines with a peculiar microbial footprint. One of the main interactions is competition for nutrients, especially nitrogen sources, that directly impacts not only fermentation performance but also the production of aroma compounds. In order to better understand the interactions taking place between non-Saccharomyces yeasts and S. cerevisiae during alcoholic fermentation, sequential inoculations of three yeast species (Pichia burtonii, Kluyveromyces marxianus, Zygoascus meyerae) with S. cerevisiae were performed individually in a synthetic medium. Different species-dependent interactions were evidenced. Indeed, the three sequential inoculations resulted in three different behaviors in terms of growth. P. burtonii and Z. meyerae declined after the inoculation of S. cerevisiae which promptly outcompeted the other two species. However, while the presence of P. burtonii did not impact the fermentation kinetics of S. cerevisiae, that of Z. meyerae rendered the overall kinetics very slow and with no clear exponential phase. K. marxianus and S. cerevisiae both declined and became undetectable before fermentation completion. The results also demonstrated that yeasts differed in their preference for nitrogen sources. Unlike Z. meyerae and P. burtonii, K. marxianus appeared to be a competitor for S. cerevisiae (as evidenced by the uptake of ammonium and amino acids), thereby explaining the resulting stuck fermentation. Nevertheless, the results suggested that competition for other nutrients (probably vitamins) occurred during the sequential inoculation of Z. meyerae with S. cerevisiae. The metabolic footprint of the non-Saccharomyces yeasts determined after 48h of fermentation remained until the end of fermentation and combined with that of S. cerevisiae. For instance, fermentations performed with K. marxianus were characterized by the formation of phenylethanol and phenylethyl acetate, while those performed with P. burtonii or Z. meyerae displayed higher production of isoamyl alcohol and ethyl esters. When considering sequential inoculation of yeasts, the nutritional requirements of the yeasts used should be carefully considered and adjusted accordingly. Finally, our chemical data suggests that the organoleptic properties of the wine are altered in a species specific manner.